Cross-Layer Path Configuration for Energy-Efficient Communication over Wireless Ad Hoc Networks - Hong-Chuan Yang; Kui Wu; Wu-Sheng Lu (Advances in Multimedia)
We study the energy-efficient configuration of multihop paths with automatic repeat request (ARQ) mechanism in wireless ad hoc networks. We adopt a cross-layer design approach and take both the quality of each radio hop and the battery capacity of each transmitting node into consideration. Under certain constraints on the maximum tolerable transmission delay and the required packet delivery ratio, we solve optimization problems to jointly schedule the transmitting power of each transmitting node and the retransmission limit over each hop. Numerical results demonstrate that the path configuration methods can either significantly reduce the average energy consumption per packet delivery or considerably extend the average lifetime of the multihop route.